2014
DOI: 10.4028/www.scientific.net/amm.607.747
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Contact Angle and Surface Tension on Copper-ABS for FDM Feedstock

Abstract: This paper presents the development of a new Copper-ABS feedstock material by the injection molding machine. The material consists of copper powder filled in an acrylonitrile butadiene styrene (ABS) binder and surfactant material. In this study, the effect of metal filled ABS and binder content on the contact angle and surface tension was investigated experimentally. The detailed formulations of compounding ratio with various combinations of a new Copper-ABS feedstock was done by volume percentage (vol. %). Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Currently, metal filled in the polymer matrix has become an alternative material used in FDM machine. Some researcher used a mix material of ABS-Iron [2,3,9,10,11] and ABS-copper [12,13]. Masood et al and Nikzad et al mentioned that the critical properties' requirements for high-quality composite are depending on the desired viscosity, strength and modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, metal filled in the polymer matrix has become an alternative material used in FDM machine. Some researcher used a mix material of ABS-Iron [2,3,9,10,11] and ABS-copper [12,13]. Masood et al and Nikzad et al mentioned that the critical properties' requirements for high-quality composite are depending on the desired viscosity, strength and modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Another study focused on developing copper-ABS filaments and determined its effect on the surface characteristics of the parts. It was found that, an improvement of the contact angle was achieved by introducing copper powder into ABS matrix [64] . A mixture of copper and iron particles was also introduced by Hwang et al [65] to investigate the thermo-mechanical properties of the new composite.…”
Section: Composite and Nano-composite Materialsmentioning
confidence: 99%
“…In addition, it is also possible to control the properties of FDM components by controlling process parameters, materials and build direction [63][64][65][66][68][69][70][71][72] .…”
Section: Potentialmentioning
confidence: 99%
“…Successful examples of developed filaments were reported for copper in acrylonitrile-butadiene-styrene copolymer (Sa'ude et al, 2013), for iron powder in polyamide (Masood and Song, 2004) and for alumina in low density polyethylene/ paraffin-based binders (Nötzel et al, 2018). The feasibility of using feedstocks filled with 47 Vol.% of zirconia powder processed by fused deposition modeling (FDM), a type of MEX technique, was investigated (Cano et al, 2019;Gonzalez-Gutierrez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%